A technology-aided program for helping persons with Alzheimer's disease perform daily activities. Issue 3 (18th September 2017) - Lancioni, Giulio; Singh, Nirbhay; O'Reilly, Mark; Sigafoos, Jeff; D'Amico, Fiora; Pinto, Katia; De Vanna, Floriana; Caffò, Alessandro
Abstract : Purpose: Persons with mild and moderate Alzheimer's disease experience increasing activity engagement failures, with consequent cognitive, social, and physical drawbacks. The purpose of this paper is to assess a technology-aided program to help these persons to independently start and carry out daily activities at the appropriate times. Design/methodology/approach: The program was implemented with eight participants according to an adapted non-concurrent multiple baseline design across participants. The program provided each participant with: timely reminders about the activities to carry out, verbal instructions about the activity steps, and brief encouragements and praise. Findings: All participants showed improvement during the program, that is, they managed to independently start the activities at the scheduled times and perform those activities with satisfactory levels of accuracy (i.e. with mean percentages of correct steps nearing or exceeding 90). Originality/value: A technology-aided program, such as that used in this study, may help persons with mild and moderate Alzheimer disease engage in daily activities, with possible benefits for their cognitive functioning, social image, and physical condition.